Geoprocessamento aplicado à análise socioambiental no alto curso da Bacia Hidrográfica do Rio Marapanim – PA - HOLANDA, Fabrício Pinto de (2022)
The high course of the Marapanim-PA river basin has undergone constant changes in its vegetation cover, given the intense agricultural activity. Thus, this work aimed to analyze the use and occupation of soil in the high course of the Marapanim river basin, between 1994, 2008 2017, through the use of geoprocessing tools and techniques. Therefore, this research is directed to the understanding of environmental impacts in the context of the basin. For this, three satellite images were used, two Landsat 5 (TM) and one landsat 8 (OLI), all of orbit-point 223-061, obtained from the website of INPE and the American Geological Service. Next, the supervised classification was performed through ArcGis 10.7, allowing the identification of the dynamics of the local vegetation cover. The variation in vegetation cover was observed from 38.11% in 1994 to 37.84% in 2017, in the same period there was an increase in the urban area by 2.09%, with the predominance of agricultural activities in the region. In the context of the basin, it is perceived that environmental guidelines are not being adequately respected, this occurs due to anthropic action together with inefficiency in the application of supervision by competent agencies.